Electron beams near surfaces: the concept of partial intensities for surface analysis and perspective on the low energy regime - Werner, Wolfgang S. M. (Frontiers in Materials, 2023)
Electron beam techniques are indispensable tools for the analysis of surfaces in fundamental as well as applied fields of science and technology. Significant improvements have been made in the past decades in the quantitative understanding of electron spectra, particularly with respect to the near-surface transport of signal electrons. The concept of partial intensities is a simple approach providing physical insight into transport of electrons in solids, a numerically convenient means for spectrum modelling and an essential ingredient for spectrum interpretation. The energy-dissipation process of energetic electrons in solids is discussed from the perspective of the partial intensities, offering a unified model for any type of electron beam technique, be it in the quasi-elastic (QE) or the continuous slowing down (CSD) regime. Examples are given for modelling and analysis of electron spectra such as X-ray photoelectron spectra (XPS), Elastic peak electron spectra (EPES) and electron energy-loss spectra (EELS). The physical model as well as the quantities for electron beam interaction with solids are reviewed, and methods for spectrum modelling and analysis are presented. The examples considered demonstrate the high level of accuracy nowadays attainable for characterisation of surfaces and nanostructures employing techniques using medium energy electrons (>100~eV). This is in contrast to the low energy regime, where a number of problems prevent a similar level of understanding. The topic of low energy electrons (LEEs) is rapidly gaining importance since in this energy range the involved electrons not only act as signal carriers, but also actively participate in electrochemical processes of importance in fields ranging from nanotechnology to life sciences. Issues of future importance in the field of LEEs are discussed and recent developments such as the 2-dimensional electron cascade in the scanning field electron microscope are highlighted.